The simultaneous perception of auditory–tactile stimuli in voluntary movement - Hao, Qiao; Ogata, Taiki; Ogawa, Ken-ichiro; Kwon, Jinhwan; Miyake, Yoshihiro (Frontiers in Psychology, 2015)
The simultaneous perception of multimodal information in the environment during voluntary movement is very important for effective reactions to the environment. Previous studies have found that voluntary movement affects the simultaneous perception of auditory and tactile stimuli. However, the results of these experiments are not completely consistent, and the differences may be attributable to methodological differences in the previous studies. In this study, we investigated the effect of voluntary movement on the simultaneous perception of auditory and tactile stimuli using a temporal order judgment task with voluntary movement, involuntary movement, and no movement. To eliminate the potential effect of stimulus predictability and the effect of spatial information associated with large-scale movement in the previous studies, we randomized the interval between the start of movement and the first stimulus, and used small-scale movement. As a result, the point of subjective simultaneity (PSS) during voluntary movement shifted from the tactile stimulus being first during involuntary movement or no movement to the auditory stimulus being first. The just noticeable difference (JND), an indicator of temporal resolution, did not differ across the three conditions. These results indicate that voluntary movement itself affects the PSS in auditory–tactile simultaneous perception, but it does not influence the JND. In the discussion of these results, we suggest that simultaneous perception may be affected by the efference copy.